Perancangan UI/UX Website Profil Desa Wisata Rancakalong dengan Metode Design Thinking - Muhamad Taufiq; Dally Nur Arif; Irena Novarlia (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Rancakalong tourist village has very diverse cultural tourism potential but faces significant challenges in development and promotion. Designing a user interface and user experience website as a medium to make it easier for tourists to make transactions and search for information. The design of the Rancakalong tourist village profile website uses a design thinking approach, which is an approach that sharpens focus and understands user experiences and needs in an effort to develop digital aspects of tourist villages in the Indonesian Tourism Village Award (ADWI). The aim of this research is to design a user interface and user experience using a design thinking approach, as well as testing the Rancakalong tourist village website using the System Usability Scale (SUS) and Single Ease Question (SEQ) testing methods. This research uses mixed methods as its research method, with a qualitative method, namely unstructured user interviews, and a quantitative method, namely usability testing. After testing, the SEQ results show that the prototype design tends to fluctuate, so slight improvements need to be made to create good usability. continued to develop real products that can provide significant benefits to the community and potential tourists as users.